Influenza A Virus Facilitates Its Infectivity by Activating p53 to Inhibit the Expression of Interferon-Induced Transmembrane Proteins - Wang, Bei; Lam, Tze Hau; Soh, Mun Kuen; Ye, Zhiyong; Chen, Jinmiao; Ren, Ee Chee (Frontiers in Immunology, 2018)
Influenza A viruses (IAV) are among the most common pathogens to cause human respiratory infections. A better understanding on interplay between IAV and host factors may provide clues for disease prevention and control. While many viruses are known to downregulate p53 upon entering the cell in order to reduce the innate host antiviral response, IAV infection is unusual in that it activates p53. However, it has not been clear whether this process has pro- or anti- viral effects. In this study, using human isogenic p53 wildtype and p53null A549 cells generated from the CRISPR/Cas9 technology, we observed that p53null cells exhibit significantly reduced viral propagation when infected with influenza A virus (strain A/Puerto Rico/8/1934 H1N1). Genome-wide microarray analysis revealed that p53 regulates the expression of a large set of interferon-inducible genes, among which the interferon-induced transmembrane family members IFITM1, IFITM2 and IFITM3 were most significantly down-regulated by the expression of p53. Knockdown of IFITMs by siRNAs enhanced influenza virus infectivity in p53null A549 cells, while overexpressed IFITMs in A549 cells blocked virus entry. Intriguingly, regulation of IFITMs by p53 is independent of its transcriptional activity, as the p53 short isoform ∆40p53 recapitulates IFITM regulation. Taken together, these data reveals that p53 activation by IAV is an essential step in maintaining its infectivity. This novel association between human p53 and the broad spectrum antiviral proteins, the IFITMs, demonstrates a previously-unrecognized mechanism employed by influenza virus to enhance its propagation via p53 inhibition of IFITMs.